Maintenance Sistem Proteksi Kebakaran Aktif Proyek Pembangunan Tangram Hotel Dan Sadira Plaza Kota Pekanbaru - Zulfikar Zulfikar; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Fire incident an accident resulting in highly detrimental both for companies, workers, and for the benefit of national development. Fire protection systems must be planned from the start simultaneously with the planning of the building constructions because of the fire protection system can not be separated from the construction of buildings. The amount of losses caused by fire sue various parties, especially the manager of an industry to perform calculations on the cost of the fire protection system maintenance on a regular basis that the warmth of the Indonesian National Standard (SNI) and international standards, namely the National Fire Protection Association (NFPA). Based on the analysis and calculation of the percentage fees for fire protection construction projects and Sadira Plaza Hotel Tangram Pekanbaru City is 3% of the contract value. While the cost of maintenance for 1 year is Rp. 847 384 814 and the cost of maintenance of fire protection for 20 years amounting to Rp. 16,947,696,297.00Key words: fire, fire protection systems, national development, maintenance costs, construction of buildings.